Standards of import / export of educational material in the distant learning (Journal of Information Technologies in Education (ITE), 2009)
The article deals with the problem of theoretical and practical material for use in distance learning, namely, adaptive systems of distance learning. Ability to transfer learning material between different systems of distance learning. The basic shortcomings of existing standards for import / export of educational material for their improvement and so on.
Keywords: adaptive process; distance learning; import / export quantum of knowledge; standards